2003
DOI: 10.1080/13693780310001610038
|View full text |Cite
|
Sign up to set email alerts
|

Production of pro-inflammatory cytokines during the early stages of experimentalParacoccidioides brasiliensisinfection

Abstract: Pro-inflammatory cytokines play an important role in both recruitment and activation of leukocytes migrating into tissues in response to invading pathogens. In this study the production of pro-inflammatory cytokines, determined by ELISA assays, and the recruitment of leukocytes into the lungs of BALB/c mice infected with Paracoccidioides brasiliensis conidia were evaluated during the early stages of infection. The results showed that infected mice had a significant increase in leukocytes in the lung during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 44 publications
2
44
0
5
Order By: Relevance
“…We have also observed that after intranasal challenge with P. brasiliensis conidia, the cellularity of bronchoalveolar lavage fluid (BAL) increased [29]. The majority of these pro-inflammatory leukocytes in BAL fluids of infected mice were PMNs.…”
Section: Inflammatory Cellsmentioning
confidence: 67%
See 1 more Smart Citation
“…We have also observed that after intranasal challenge with P. brasiliensis conidia, the cellularity of bronchoalveolar lavage fluid (BAL) increased [29]. The majority of these pro-inflammatory leukocytes in BAL fluids of infected mice were PMNs.…”
Section: Inflammatory Cellsmentioning
confidence: 67%
“…Even if the early inflammatory response is nonspecific, such a stage is important because it is just at this moment that the resident pulmonary macrophages interact with the fungus for the first time and become activated proceeding to stimulate recruitment of other inflammatory cells [27][28][29][30]. In summary, the observations described above establish the value of this animal model for studies of the immune responses in PCM, and may contribute to designing new, more far reaching experiments.…”
Section: Introductionmentioning
confidence: 96%
“…As citocinas pró-inflamatórias, como fator de nec rose tumoral alfa (TNF-alfa), IL-6, IL-1 beta e pro t e í n a inflamatória do macrófago (MIP) 2, seriam re s p o n s á-veis pelo re c rutamento de leucócitos em nível pulmon a r, durante a fase inicial da infecção e influenciariam na organização da resposta imune, na presença do fungo 10 .…”
Section: Fig 1 Rm Do Encéfalo Com Imagens Ponderadas Em T1 E Contrasunclassified
“…A coleção dos conídios para experimentação normalmente é feita por dois métodos: o método de lã de vidro e a purificação por gradientes de percoll (18,100,101). Nós trabalhamos somente com purificação por lã de vidro, que é a metodologia mais apropriada para o trabalho com modelo animal.…”
Section: Coleta E Purificação De Conídiosunclassified
“…Para a infecção com propágulos foi adotado o modelo da infecção intranasal descrito previamente (20,100,105). Os animais foram anestesiados e, quando se apresentaram insensíveis à dor, os conídios, cuja concentração foi ajustada para 4x10 6 células/60µl, foi administrada intranasalmente (i.n.)…”
Section: Infecção Intranasal Com Propágulosunclassified